Implementasi Pembelajaran Motivasi, Kreativitas dan Inovasi dalam Meningkatkan Daya Saing Usaha Kamsi Boba di Tengah Pandemi Covid-19 - Benny Helika Samudra (EduPsyCouns: Journal of Education, Psychology and Counseling, 2021)
The superiority of covid-19 spread throughout the world including Bangkalan Regency. Abdullah as the business owner of Kamsia Boba precisely on the road RE Martadinata was slump because this pandemic. The existence of this pandemic caused competitiveness to decline so that sales fell drastically, with motivation, creativity and innovation explored by Abdullah to maintain his bussiness gradually sector was able to survive and remain effective.